Names of video games related to their technical characteristics - Kaszewski, Krzysztof (Papers in Linguistics, 2025)
The aim of the article is to show names of video games referring to their technical side currently available in the Polish-language specialist media. Examples collected from popular Polish web portals and the latest traditional (paper) magazines showed that there are over forty such units and they concern various aspects of games: the necessary hardware, software and the production process. Most of them are not recorded in general dictionaries of the Polish language, nor are they discussed in scientific studies. The presented research increases the knowledge on the lexical resources of the Polish language; the comparison of names used in communication practice also helps to see what is not present yet in language and discourse, i.e. what names we do not use, even though we could use them.